Autonomic Neural Circuit and Intervention for Comorbidity Anxiety and Cardiovascular Disease - Chen, Xuanzhao; Xu, Li; Li, Zeyan (Frontiers in Physiology, 2022)
Anxiety disorder is a prevalent psychiatric disease and imposes a significant influence on cardiovascular disease (CVD). Numerous evidence support that anxiety contributes to the onset and progression of various CVDs through different physiological and behavioral mechanisms. However, the exact role of nuclei and the association between the neural circuit and anxiety disorder in CVD remains unknown. Several anxiety-related nuclei, including that of the amygdala, hippocampus, bed nucleus of stria terminalis, and medial prefrontal cortex, along with the relevant neural circuit are crucial in CVD. A strong connection between these nuclei and the autonomic nervous system has been proven. Therefore, anxiety may influence CVD through these autonomic neural circuits consisting of anxiety-related nuclei and the autonomic nervous system. Neuromodulation, which can offer targeted intervention on these nuclei, may promote the development of treatment for comorbidities of CVD and anxiety disorders. The present review focuses on the association between anxiety-relevant nuclei and CVD, as well as discusses several non-invasive neuromodulations which may treat anxiety and CVD.